The influence of technological methods of growing corn with legumes on the nutritional value of silage raw materials - Тарасов, Олександр; Свистунова, Ирина; Полторецкий, Сергей; Гладиш, Андрій; Божок, Юлія; Гайдай, Алла; Гудзь, Наталія (SWorldJournal, 2022)
The results of research on the study of the influence of technological methods of growing mixed corn crops with high-protein crops on silage on the nutritional value of silage raw materials are outlined. It was established that according to the collection